PS 14-51 PSYCHOMOTOR IMPAIRMENT IN PATIENTS TAKING ANTIHYPERTENSIVE MEDICINES IN INDIA. (September 2016) - Mutneja, Ekta; Gupta, Pooja; Yadav, Rakesh; Dey, Aparajit Ballabh; Gupta, Yogendra Kumar
Abstract : Objective: To assess the effect of antihypertensive medicines and severity of hypertension on psychomotor performance of patients undergoing medicinal therapy. Design and Method: A cross-sectional study was conducted for six months at a tertiary care referral hospital among patients attending geriatric and cardiac outpatient departments who were on antihypertensive therapy. The study was approved by institute ethics committee and patients were enrolled with prior informed consent. A battery of five pen paper tests (Trail Making Test-A/B, Digit Symbol Substitution Test, Standardized Mini Mental State Examination, Word Recall Test and Wisconsin Card Sorting Test (WCST)) was used to assess various domains of psychomotor performance. The psychomotor scores were calculated and compared with the severity of hypertension and with different antihypertensive classes of medicines. Results: The enrolled 402 patients had mean age of 54 ±13.7 years (68% males). Of these, 5.2% had blood pressure in the normal range after the median treatment duration of 3 years(IQR 1.5–6 years) with antihypertensive medicines. Of the total patients, 38.8% were in stage I hypertension, 28.1% in prehypertensive stage and 27.9% in stage II hypertension. The most commonly prescribed antihypertensive medicines were angiotensin blockers (Angiotensin converting enzyme inhibitors and angiotensin receptor blockers) followed by β-blocker (55.7%), diuretics (42.3%) and calcium channel blockers (CCBs; 34.1%). Psychomotor performance test scores did not vary significantly with the severity of hypertension. However, the WCST scores varied significantly for patients prescribed β-blockers and CCBs.β-blockers followed by CCBs and other drug such as α-blockers and α+β-blockers were associated with poor psychomotor performance in hypertensive patients (Table 1). Conclusions: Different classes of antihypertensive medicines variably affect the psychomotor performance. Although larger studies controlled for confounders like duration of hypertension, concomitant diseases, age etc. are need, the observations should be borne in mind while prescribe antihypertensive medicines to patients at risk of psychomotor impairment and those requiring high levels of alertness.